Comprehensive analysis of the large and small ribosomal proteins in breast cancer: Insights on proteomic and transcriptomic expression patterns, regulation, mutational landscape, and prognostic significance. (October 2022) - Azevedo, Alexandre Luiz Korte de; Gomig, Talita Helen Bombardelli; Giner, Igor Samesima; Batista, Michel; Marchini, Fabricio Klerynton; Lima, Rubens Silveira; Urban, Cícero de Andrade; Sebastião, Ana Paula Martins; Cavalli, Iglenir João; Ribeiro, Enilze Maria de Souza Fonseca
Abstract: Several evidence has demonstrated the involvement of the ribosomal proteins (RPs) in many malignancies, however, the function and clinical relevance of the RPs in breast cancer remains unclear. The present study aims to contribute to the understanding of the role of the RPs in breast tumorigenesis and its clinical implications in the field of biomarker discovery and outcome prediction. We investigated the proteomic and transcriptomic expression of the RPs in non-tumor and tumor tissues of different breast cancer subtypes, and integrated bioinformatics approaches and online databases to comprehensively evaluate the potential functions, regulatory networks, mutational landscape, and prognostic values of the ribosomal proteins in breast cancer. Our results show that 33 RPs have deregulated expression in breast cancer and its subtypes and that 26 RPs have potential as prognostic markers in a subtype-dependent way, with mutations in RP genes being frequent in breast tumors and related to overall survival and relapse-free status. Our RP gene regulatory network indicates the transcription factors MYC, ETS1, and SPI1, and the miRNAs has-let-7c-5p, has-mir-20b-5p, and has-mir-4668–3p as regulators of the RPs expression in breast cancer. The RPs were associated with several clinicopathological parameters of breast cancer and predicted to be involved in ribosomal-independent mechanisms such as regulation of the SLITS-ROBO pathway. This study comprehensively investigated the ribosomal proteins in breast cancer, suggesting that the RPs have clinical potential as biomarkers of diagnostic and prognostic, also providing an in-depth view of the RPs significance in breast cancer. Graphical Abstract: ga1 Highlights: Each subtype presents a particular pattern of ribosomal proteins expression. The ribosomal proteins are related to patient's survival and prognosis. Mutations in its genes are frequent and are related patients' prognosis. These proteins are involved in processes beyond translation in breast cancer. We also appoint the main regulators of ribosomal proteins expression.